Reduced Expiratory Flow Rate among Heavy Smokers Increases Lung Cancer Risk. Results from the National Lung Screening Trial–American College of Radiology Imaging Network Cohort - Hopkins, Raewyn J. (Ann Am Thorac Soc, 2017)
Rationale: Although epidemiological studies consistently show that chronic obstructive pulmonary disease is associated with an increased risk of lung cancer, debate exists as to whether there is a linear relationship between the severity of airflow limitation and lung cancer risk. Objectives: We examined this in a large, prospective study of older heavy smokers from the American College of Radiology Imaging Network subcohort of the National Lung Screening Trial (ACRIN). Airflow limitation was defined by prebronchodilator spirometry subgrouped according to Global Initiative for Chronic Obstructive Lung Disease (GOLD) grades 1–4. Methods: In the National Lung Screening Trial–ACRIN cohort of 18,473 screening participants, 6,436 had airflow limitation (35%) and 12,037 (65%) had no airflow limitation. From these groups, 758 lung cancer cases were prospectively identified. Participants with airflow limitation were stratified according to GOLD groups 1 (n = 1,607), 2 (n = 3,528), 3 (n = 1,083), and 4 (n = 211). Lung cancer incidence at study end (mean follow-up, 6.4 yr) was compared between the GOLD groups and those with no airflow limitation (referent group). Measurements and Main Results: Compared with those with no airflow limitation, where lung cancer incidence was 3.78/1,000 person years, incidence rates increased in a simple linear relationship: GOLD 1 (6.27/1,000 person yr); GOLD 2 (7.86/1,000 person yr); GOLD 3 (10.71/1,000 person yr); and GOLD 4 (13.25/1,000 person yr). All relationships were significant versus the reference group at a P value of 0.0001 or less. Conclusions: In a large prospective study of high-risk cigarette smokers, we report a strong linear relationship between increasing severity of airflow limitation and risk of lung cancer.